Internalization of Pragmatic Education in Rahmatan Lil 'Alamin Islamic Religious Culture for Students in Educational Institutions - Ridwan Efend Ridwan Efend (Auladuna : Jurnal Prodi Pendidikan Guru Madrasah Ibtidaiyah, 2022)
ABSTRACT (ENGLISH) This study aims to describe the internalization of pragmatic education in the Islamic religious culture of Rahmatan Lil'alamiin students at the State Junior High School 1 Sumbermalang. The research method uses qualitative. Determination of informants using purposive sampling. The data collection uses interview, observation, and documentation techniques. The data analysis uses the Miles & Haberman technique, namely data collection, data reduction, data display and conclusion drawing. The validity of the data uses source triangulation. The results of this study indicate the following: 1) habituation of prayer, such as the obligatory Duha prayer and Duhur prayer at school. PAI teachers emphasize how important prayer is for human spiritual needs, so teachers require congregational prayers at school so that students are also accustomed to praying together at home; 2) get used to harmonious relationships between children and other people. the teacher accustoms students to have empathy for others because humans are creatures who need each other; and 3) getting used to good relations between students and nature. Schools usually hold a "plant of a thousand trees" once a year. This activity was carried out during the 17th anniversary of August, all teachers and students together planted trees on the slopes of Mount Ragopuro Sumbermalang, with the aim of reforesting bare forests so that there are no natural disasters that can harm the local environment and society. ABSTRAK (INDONESIA) Penelitian ini bertujuan untuk mendiskripsikan internalisasi pendidikan pragmatik dalam budaya religius Islam Rahmatan Lil’alamiin anak didik di Sekolah Menengah Pertama Negeri 1 Sumbermalang. Metode penelitian menggunakan kualitatif. Penentuan informannya menggunakan purposive sampling. Pengumpulan datanya menggunakan teknik wawancara, observasi, dan dokumentasi. Analisa datanya menggunakan teknik miles&Haberman yaitu pengumpulan data, reduksi data, display data dan penarikan kesimpulan. Keabsahan datanya menggunakan triangulasi sumber. Hasil penelitian ini menunjukkan sebagai berikut: 1) pembiasaan sholat, seperti wajibnya sholat dhuha dan sholat duhur di sekolah. Guru PAI menekankan betapa pentingnya sholat untuk kebutuhan rohani manusia, sehingga guru mewajibkan sholat berjamaah di sekolah agar anak didik juga terbiasa melakukan sholat berjamaah di rumah; 2) membiasakan hubungan yang harnomis antara anak dengan dengan orang lain. guru membiasakan anak didik untuk mempunyai sifat empati kepada sesama karena manusia adalah makhluk yang saling membutuhkan satu sama lain; dan 3) membiasakan hubungan baik antara anak didik dengan alam. Sekolah biasanya setahun sekali mengadakan kegiatan “tanaman seribu pohon”. Kegiatan ini dilakukan pada saat HUT 17 agustus, semua guru dan anak didik bersama-sama menanam pohon di lereng gunung ragopuro Sumbermalang, dengan tujuan penghijauan hutan yang gundul agar tidak ada bencana alam yang bisa membahayakan lingkungan setempat dan masyarakat.